Sur la corde raide de l’éthique - Desjardins, Guy (Assurances, 1989)
Our collaborator, Me Guy Desjardins, has examined the ethical problems faced by lawyers who are chosen by the Insurer to represent an Insured. The lawyer may on many occasions have to contend with the dilemma of acting in the interest of the Insured or that of his principal. In his article, Me Desjardins examines a number of decisions handed down by our courts and involving this question. According to the author, it is useful to closely analyze these decisions so that lawyers who are regularly appointed by their insurers to represent insureds are able to better appreciate the problems such a mandate may entail and therefore allow them to take the necessary steps to avoid making a faux pas.